2019
DOI: 10.1007/s40093-019-00291-x
|View full text |Cite
|
Sign up to set email alerts
|

Enriched animal manure as a source of phosphorus in sustainable agriculture

Abstract: Purpose Due to the pressures of conforming to environmental quality standards and the increased costs of mineral fertilizer importation, there is growing interest in the use of organic residues as fertilizers. To test the hypothesis that indicates the quantity of animal manure (AM) depends on the phosphorus (P) needs of the crops, an experiment was run using three organic animal manures (chicken-CM, turkey-TM, and cow manure-CoM), enriched with limestone, gypsum, and phosphorus. Methods A greenhouse experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…Hoang and Marschner (2019) demonstrated the influence of mature barley straw applications in the soil on microbial biomass P becoming an important P source for plants. These results indicate that organic matter plays a role as a regulator of available P, avoiding P losses to the environment (Cabeza et al 2019;Li and Marschner 2019;Almeida et al 2019). In our study, the association of liming with HA lowered the amount of extracted Pi BIC and Pi HID-0.1 , probably due to the P-Fe-HA complex formation as demonstrated by Sinha (1971) and Gerke and Hermann (1992).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Hoang and Marschner (2019) demonstrated the influence of mature barley straw applications in the soil on microbial biomass P becoming an important P source for plants. These results indicate that organic matter plays a role as a regulator of available P, avoiding P losses to the environment (Cabeza et al 2019;Li and Marschner 2019;Almeida et al 2019). In our study, the association of liming with HA lowered the amount of extracted Pi BIC and Pi HID-0.1 , probably due to the P-Fe-HA complex formation as demonstrated by Sinha (1971) and Gerke and Hermann (1992).…”
Section: Discussionsupporting
confidence: 62%
“…High rates of organic and inorganic fertilizers are used to minimize P immobilization effect on crop production (Yadesa et al 2019;Mota et al 2019;Almeida et al 2019). Withers et al (2018) demonstrated that an application of 35 kg P ha −1 is required to overcome soil P immobilization in new areas, and a constant application of 25.2 kg P ha −1 year −1 to maintain crop production in savanna soils of Brazil (Cerrado).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above discussion, we also realize that agronomic efficiency of animal-derived fertilizers is highly dependent on its N availability. In contrast, various studies considered animal waste as a source of P in sustainable agriculture [42,75,106]. Judicious use of animal manures maximizes economic returns increasing crop yield per unit of fertilizer applied [107].…”
Section: Dose Calculation and Yield Potential Assessmentmentioning
confidence: 99%
“…Another report [23] indicated that P content of poultry manure was higher than those of goat and cattle manures, ranged from 0.2 to 1.1 %. Higher P contents in all animal-feces LOFs compared to P content in solid manures might be due to addition of Tithonia diversifolia used in the production of LOF which accounted by is 0.87% [8].…”
Section: Effects On Phosphorus Content (%)mentioning
confidence: 99%
“…Each feces might have different nutrient contents since each animal digests different types of foods during their courses of growth and development, which eventually produce different nutrient properties in their feces. Animal manures are the potential to supply nutrients for sustainable production practices, especially P, Ca, Mg, and K for plants [8]. Amending cow manure into the soil appeared to be the most viable option to improve the phosphorus and organic matter in soil because of high C/N.…”
Section: Introductionmentioning
confidence: 99%